2021
DOI: 10.3390/antibiotics10121538
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Isolates from Cattle with Bovine Respiratory Disease in Bavaria, Germany

Abstract: Patterns of antimicrobial resistance (AMR) regarding Pasteurella multocida (n = 345), Mannheimia haemolytica (n = 273), Truperella pyogenes (n = 119), and Bibersteinia trehalosi (n = 17) isolated from calves, cattle and dairy cows with putative bovine respiratory disease syndrome were determined. The aim of this study was to investigate temporal trends in AMR and the influence of epidemiological parameters for the geographic origin in Bavaria, Germany, between July 2015 and June 2020. Spectinomycin was the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Economic losses due to treatment costs and reduced weight gain in beef production [55,56], as well as decreased milk yield and other negative effects on dairy cow health [57][58][59], highlight the importance of treatment options for infections caused by these two pathogens; especially, since multidrug-resistant (MDR) isolates are increasingly isolated from cattle with bovine respiratory disease (BRD). In Germany, the rates of MDR isolates have increased more than six-fold in P. multocida within a five-year period (2015-2020) [60]. That study reported MDR rates of 13.9% and 5.1%, while rates of pan-susceptibility were only 15.1% and 12.1% in isolates of P. multocida and M. haemolytica, respectively [60].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Economic losses due to treatment costs and reduced weight gain in beef production [55,56], as well as decreased milk yield and other negative effects on dairy cow health [57][58][59], highlight the importance of treatment options for infections caused by these two pathogens; especially, since multidrug-resistant (MDR) isolates are increasingly isolated from cattle with bovine respiratory disease (BRD). In Germany, the rates of MDR isolates have increased more than six-fold in P. multocida within a five-year period (2015-2020) [60]. That study reported MDR rates of 13.9% and 5.1%, while rates of pan-susceptibility were only 15.1% and 12.1% in isolates of P. multocida and M. haemolytica, respectively [60].…”
Section: Discussionmentioning
confidence: 98%
“…In Germany, the rates of MDR isolates have increased more than six-fold in P. multocida within a five-year period (2015-2020) [60]. That study reported MDR rates of 13.9% and 5.1%, while rates of pan-susceptibility were only 15.1% and 12.1% in isolates of P. multocida and M. haemolytica, respectively [60]. Another recent study identified a novel high-level macrolide resistance determinant in M. haemolytica, further limiting treatment options for BRD [61].…”
Section: Discussionmentioning
confidence: 99%
“…Bovine respiratory disease (BRD), the leading cause of morbidity and mortality in U.S. beef cattle ( 1 ), poses a threat to cattle operations. The prevalence of antimicrobial resistance (AMR) appears to be increasing in Mannheimia haemolytica ( M. haemolytica ), a leading contributor to BRD ( 2 4 ); research is underway to determine the causes and impact of AMR in M. haemolytica . Characterization of the AMR phenotype by culture and antimicrobial susceptibility testing is complicated by uncertainty regarding the number of M. haemolytica colonies that must be selected to adequately characterize antimicrobial susceptibility phenotypes (antibiograms) and genotypes in a sample.…”
Section: Introductionmentioning
confidence: 99%